ANALISIS SISTEM PERAWATAN KOMPONEN TWIST LOCK PADA UNIT CONTAINER CRANE DI TERMINAL PETI KEMAS PT PELINDO IV BITUNG - Pabasing, Sandy; Arungpadang, Tritiya A.R.; Mende, Jefferson (Jurnal Tekno Mesin, 2024)
The twist lock component in the container crane unit is a component that plays an important role in the loading and unloading process for which maintenance is needed, so the purpose of this study is to determine the system and type of treatment applied to the twist lock component at PT. Pelindo IV Bitung by using descriptive qualitative research methods to obtain data information obtained using primary and secondary data. The results of the research data processing obtained the relationship between the maintenance of twist lock components with the loading and unloading process which is very important to be carried out for the smooth loading and unloading process and the cessation of loading and unloading process activities due to damage to the twist lock components. So that the maintenance system applied to the twist lock component of the container crane unit is; Routine inspection, lubrication, cleaning, replacement, function testing, maintenance records and having two types of maintenance applied to twist lock components namely breakdown maintenance and preventive maintenance. Keywords: Maintenance System, Twist Lock, Container Crane ABSTRAK Komponen twist lock pada unit container crane merupakan komponen yang berperan penting dalam proses bongkar muat untuk itu di perlukan perawatan, sehingga tujuan dari penelitian ini untuk mengetahui sistem dan jenis perawatan yang diterapkan pada komponen twist lock di PT. Pelindo IV Bitung dengan menggunakan metode penelitian kualitatif deskriptif untuk memperoleh infomasi data diperoleh dengan menggunakan data primer dan sekunder. Hasil pengolahan data penelitan diperoleh hubungan perawatan komponen twist lock dengan proses bongkar muat yang sangat penting dilakukan untuk kelancaran proses bongkar muat dan terhentinya kegiatan proses bongkar muat akibat kerusakan-kerusakan pada komponen twist lock. Sehingga sistem perawatan yang diterapkan pada komponen twist lock unit container crane yaitu; inspeksi rutin, pelumasan, pembersihan, penggantian, pengujian fungsi, catatan perawatan dan memiliki dua jenis perawatan yang diterapkan pada komponen twist lock yaitu breakdown maintenance dan preventive maintenance. Kata Kunci: Sistem Perawatan, Twist Lock, Container Crane